Inhibition of MTA1 by ERα contributes to protection hepatocellular carcinoma from tumor proliferation and metastasis. Issue 1 (December 2015) - Deng, Lei; Yang, Hui; Tang, Junwei; Lin, Zhe; Yin, Aihong; Gao, Yun; Wang, Xuehao; Jiang, Runqiu; Sun, Beicheng
Abstract Background Although expression of MTA1 inversely correlates with the nuclear localization of ERα, the effect and molecular mechanism of ERα regulation of MTA1 remain unknown. Methods Quantitative real-time PCR and western blot analyses were used to measure levels of MTA1. The effect on HCC cell proliferation and invasion was assessed by EdU incorporation assays and Transwell, respectively. ShRNA and dual-luciferase assays were used to investigate the regulatory relationship between MTA1 and ERα in cell lines. Results We found that MTA1 gene regulation by ERα may be influenced by nuclear corepressors. The MTA1 promoter has three functional ER-element half-sites that lead to decreased MTA1 transcription and expression. ERα overexpression suppressed the proliferation and invasion of hepatocellular carcinoma cells (HCC). In addition, overexpression of MTA1 attenuated ERα-mediated suppression of the proliferation and invasion of HCC cells and tumor formation in vivo. These results suggested feedback regulation between ERα and MTA1. In summary, our results demonstrated that ERα suppressed proliferation and invasion of human HCC cells through downregulation of MTA1 transcription. Conclusions Our study is an improved description of the mechanisms of the suppressive effect of ERα on HCCs, adding understanding to the gender disparity of HCC progression.